MEASURING CUSTOMER TRUST THROUGH DIGITAL TRANSFORMATION OF BANKING AS A COMPETITIVE ADVANTAGE - Pristiyono, Pristiyono; Juliana, Juliana; Prayoga, Yudi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The financial and banking industry has implemented digitalization as a marketing weapon and realized industry 4.0. The purpose of this study was to determine the extent of the implementation of banking digitalization in the expansion areas. The population of this research is the customers registered at Bank Sinar Mas Rantauprapat in 2021 as many as 1445 people. Research using multivariate data should use the number of samples in the survey as many as 200 samples with purposive sampling technique. Smart PLS data analysis through the stages of convergent validity, discriminant, composite reliability, Cronbach's alpha and R-square. The results show that customer trust is very important in the business practice of the financial or banking industry, this is because customer trust is the most effective weapon in the banking service industry based on digital transformation as banking services will be able to increase customer satisfaction and even loyalty and attract new customers. Digital transformation in the banking world is an important phenomenon as access to the realization of customer-company interactions through information and communication technology, making it easier for companies to win the competition and become a competitive advantage for banking.